The complete plastid genome of the middle Asian endemic of Stipa lipskyi (Poaceae). (1st November 2016) - Myszczyński, Kamil; Nobis, Marcin; Szczecinska, Monika; Sawicki, Jakub; Nowak, Arkadiusz
Abstract: The structure of the Stipa lipskyi (GenBank accession no. KT692644) plastid genome is similar to that of closely related Poaceae species: it has a total length of 137 755 bp, the base composition of the plastome is the following: A (30.7%), C (19.3%), G (19.4%) and T (30.5%). The S. lipskyi plastid genome contains 71 genes, excluding second IR region. A complete plastome sequence of S. lipskyi will help the development of primers for examining phylogeny and hybridization events in this taxonomically difficult genus.